Inferiority Complex and Striving for Superiority in Sayaka Murata’s Convenience Store Woman - Wardah, Dewi (Journal of Literature, Linguistics, & Cultural Studies, 2024)
The issue that occur within a person, such as feeling inferior, are things that still exist today. It happens because there are factors where someone ultimately being an inferiority person because they are not the same as other people. Those even become an inferiority complex. The issue of inferiority is reflected in the novel by Sayaka Murata entitled Convenience Store Woman, which describes the complex inferiority experienced by the main character, Keiko Furukura. This research aims to find out the causes of the inferiority complex experienced by the main character, as well as how the main character struggles towards his superiority (striving for superiority). This research uses literary criticism with novels as the object of research and use a psychological approach with the theory of individual psychology put forward by Alfred Adler which discusses human behavior seen as compensation for feelings of inferiority. The purpose of human life seems to be overcoming feelings of inferiority towards a striving for superiority. The results of this research revealed that Keiko experienced an inferiority complex caused by other people when she was at school and at workplace and also caused by her personality. Then, she finally finds the ways to overcome her inferiority by being herself and continuing to work as a convenience store worker as a form of striving for superiority. In addition, the suggestions from researcher that further researchers explore this novel using other approaches and criticsm to take more different perspective.